Prescription pattern of antibiotics in hospital discharge summaries of a tertiary care hospital in India: a cross-sectional study - Nazir, Tabinda; Ashai, Zubair; Tabassum, Rehana; Ayoub, Idrees (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Particularly in poor and developing nations, antibiotics have a remarkable role in extending life. Inappropriate antibiotic prescribing methods are implicated by a number of factors, including a lack of communication between the doctor, pharmacist, and patients, peer pressure and patient demands, diagnostic uncertainty, and inadequate expertise among clinicians. Aim of this study was to observe pattern of antibiotic prescribing in discharge summaries of admitted patients. Methods: A cross sectional IPD based study was carried out in a tertiary care hospital of north India for a period of 3 months.500 discharges were collected and data regarding antibiotic prescribing was analysed in the form of Name, and route of the antibiotic prescribed, usage of multiple antibiotics, usage of prophylactic antibiotic, prescribing of antibiotics according to access watch and reserve. The recorded data was then compiled in spreadsheet (Microsoft Excel) and then exported to data editor of SPSS Version 29.0 and R software. Results: Total 500 discharge summaries were analysed. A total of 468 (93.6%) antibiotics were prescribed. Females were prescribed a high number of antibiotics compared with males. Antibiotics were prescribed most commonly to patients of >60 years of age. Out of 468 antibiotics (101) antibiotics were from ACCESS group 314 from WATCH group and 53 from RESERVE. Percentage of drugs prescribed by generic name was 1.6%.58.4% of prescriptions had a single antibiotic, and 16.6% of the population have received multiple antibiotics. Conclusions: Out of 500 prescriptions analysed 468 prescriptions had antibiotics prescribed which constituted a percentage of about 93.6% exceeding the WHO limit of 30% suggestive of irrational antibiotic prescribing. WATCH group of antibiotics constituted the highest number according to AWaRe which is a concern since these antibiotics have higher resistance potential and includes highest priority agents among antibiotics. Awareness among the physicians must be boosted up in this regard. Strict implementation of the use of standard treatment guidelines and Adherence to AWaRe prevents inappropriate prescribing. To combat antibiotic resistance such studies should be continued and proper auditing after every 3 months should be implemented.